Selective Serotonin Reuptake Inhibitors for Cessation of Betel Quid Use in Patients with Major Depressive Disorder in Taiwan - Chung-Chieh Hung; Hung-Pin Tu; Chia-Min Chung (Biomedicines, 2024)
Background/Objectives: Major depressive disorder (MDD) frequently co-occurs with substance use disorders such as alcohol and nicotine use disorders. Comorbid substance use disorders worsen the clinical symptoms of MDD and exacerbate addictive behaviors and presentations. However, the relationship between MDD and betel quid use disorder (BUD) in Taiwan has not been extensively investigated. Methods: We performed this cross-sectional study investigated associations between betel quid use, BUD, and MDD specifically in the Taiwanese population. Long-term betel quid use is a major public health concern, contributing significantly to the high incidence of oral cancers, which rank fifth among the top ten most common cancers in Taiwan. Results: Among patients with MDD, the current BUD prevalence rate was 7.32%, and the lifetime BUD prevalence rate was 15.45%. Patients with comorbid BUD were more likely to have severe alcohol and nicotine dependence disorders and required longer antidepressant treatment. Conclusions: Notably, 16.98% of patients with comorbid BUD who received selective serotonin reuptake inhibitor treatment achieved abstinence. BUD has a detrimental effect on health outcomes in patients with MDD, and selective serotonin reuptake inhibitor treatment may be required to be prolonged for betel quid abstinence therapy to be effective. Additional studies should investigate medication therapies for betel quid addiction disorders.